Centro de exposición con tendencias temáticas para espacios del hogar - Cadena Moreno, Génesis Fernanda (2015)
In the way of designing and building, the interior architecture seeks to offer the human being satisfaction, allows creating spaces that go according to the daily necessities, taking into account the activity and geographical location. In order to give greater comfort to those who occupy the spaces, the design must comply with functionality and care to the environment. It proposes to propose an exhibition center with thematic tendencies for spaces of the hearth in a warehouse located in the Parroquia El Rosario, industrial sector of the city of Quito. The interior design proposal is aimed at showing the public the relational trends as a project of furniture and interior architecture, as well as the process of designing them. Through this research document you can create more spaces for the exhibition and development of trends for home spaces. It also seeks a mission that justifies the creation of an establishment in the chosen area. The purpose of this project is to build on the knowledge of interior architecture through the exhibition of furniture and trends in relation to home spaces, providing the professional and public several areas to observe and design, with the help of professionals. Through the analysis of the information, a new image of the place can be constructed to promote the use of new furniture, materials and trends in the user.